1991
DOI: 10.1063/1.461383
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid immiscibility loops predicted with the simplified-perturbed-hard-chain theory

Abstract: In this study, it will be shown that in binary mixtures, type VI phase behavior, according to the classification of van Konynenburg and Scott [Philos. Trans. R. Soc. London, Ser. A 298,495 (1980)], can be obtained from a simple, semitheoretical equation of state. The applied equation of state was derived from the simplified-perturbed-hard-chain theory (SPHCT). In literature, there are no known examples of type VI phase behavior being obtained from a simple equation of state. In addition, the systematic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…The analytical method of derivation for various liquid-gas equations of state shows the same main types of fl uid phase behavior for different kind of molecular interactions and the same sequences of transformation of one type of binary phase diagram into another due to continuous alteration of molecular parameters in the equations of state (Scott and van Konynenburg, 1970;Boshkov, 1987;Deiters and Pegg 1989;van Pelt et al, 1991;Harvey, 1991;Kraska and Deiters, 1992;Kraska, 1998, 1999a,b;Yelash et al, 1999;Kolafa et al, 1999). Most of the types of fl uid phase behavior described by Van der Waals and his school as well as by recent experimentalists can be recognized in analytically derived global phase diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical method of derivation for various liquid-gas equations of state shows the same main types of fl uid phase behavior for different kind of molecular interactions and the same sequences of transformation of one type of binary phase diagram into another due to continuous alteration of molecular parameters in the equations of state (Scott and van Konynenburg, 1970;Boshkov, 1987;Deiters and Pegg 1989;van Pelt et al, 1991;Harvey, 1991;Kraska and Deiters, 1992;Kraska, 1998, 1999a,b;Yelash et al, 1999;Kolafa et al, 1999). Most of the types of fl uid phase behavior described by Van der Waals and his school as well as by recent experimentalists can be recognized in analytically derived global phase diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…Bolz 23 recently performed comparative global phase behavior calculations for the van der Waals and Redlich-Kwong equation of state. van Pelt et al 24 calculated closed loop liquid-liquid immiscibility with the simplified-perturbed hard-chain theory ͑SPHCT͒ equation. A new type of binary fluid phase behavior, type VIII, was calculated by the interference of the high pressure critical curve with critical curves at low pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Type IV or V behavior can be consid- This transitional status is reflected in the sensitivity of the adjustable parameters required to predict the appropriate critical properties. Boshkov (1987), Deiters and Pegg (1990), van Pelt et al (1991), and Smith et al (1989) demonstrated that all of the known phase behavior types exhibited by binary mixtures can be qualitatively reproduced if a suitable model is used. For example, Boshkov (1987) It is probable that many noncubic equations of state can be used for such calculations.…”
Section: Other Phenomenamentioning
confidence: 99%